Intrauterine device (IUD) migration to the fallopian tube: a rare location for a translocated IUD with no visceral injury - Peter Joseph Wangwe; Najma Awadh; Magreth Angelus (BMC, 2024)
Abstract Background Loss of Intra Uterine Device (IUD) following silent perforation of the uterus either during or after IUD insertion is an uncommon finding due to a lack of immediate follow-up. We report a rare case in which uterine perforation following the migration of IUD to the right fallopian tube without visceral injury. The patient presented with lower abdominal pain and pain during sex for one year since IUD insertion. On examination, we noted tenderness on the right suprapubic region and on speculum examination, no IUD thread was seen. A radiological pelvic examination showed an empty uterus without an IUD. Laparotomy and retrieval of migrated IUD was done followed by repair of perforated uterus. Conclusion Migrated IUD with silent uterine perforation without visceral injury is a distressing clinical condition both to the patient and the clinician. This case is reported to increase awareness in doing immediate vaginal examination and pelvic ultrasound post-IUD insertion.